A Systematic Analysis of a Small-Scale HAWT Configuration and Aerodynamic Performance Optimization Through Kriging, Factorial, and RSM Methods - Farzad Ghafoorian; Hui Wan; Sahel Chegini (Journal of Applied and Computational Mechanics, 2025)
The growth of greenhouse gases and the limitations linked to fossil fuels have intensified the drive to exploit renewable energy sources. Wind energy has emerged as an accessible and cost-effective clean energy solution, attracting the attention of scientists. Horizontal axis wind turbines (HAWTs) are widely recognized as a common turbomachine for generating power from wind energy. Nevertheless, enhancing the system’s efficiency remains crucial. In this research, a small-scale HAWT is numerically studied using Qblade, a commercial code coupling the blade element momentum (BEM) approach with the actuator disc theory. This study explores the impact of design parameters, including rotor diameter, hub diameter, blade number, blade chord length distribution, twist angle distribution, and airfoil profile, on the turbine power coefficient. Subsequently, optimization efforts are applied to the results obtained for a 3-blade rotor with SG6043 airfoil profile using three distinct optimization methods: Kriging, factorial, and the classical polynomial Response Surface Method (RSM). The proposed geometries generated by the Kriging, factorial, and RSM methods are numerically analyzed using Qblade, yielding maximum Cp values of 0.450, 0.478, and 0.447 respectively. These values represent a respective improvement of 5.6%, 11%, and 5% compared to the base geometry, which had a Cp value of 0.425.